Bahasa Sembang in web forums: knowledge management for piles of atopian discourse - Abd. Rozan, Mohd. Zaidi; Mikami, Yoshiki (2006)
The popularity of web forums has led to the creation of evolutionised bahasa Melayu (BM) known as sembang language. Greatly accepted as common and sensible vocabularies for its communities, sembang language has emerged as an avenue that supports knowledge-sharing-procreation practice. In this paper, we are trying to explore the fact that bahasa sembang could serve as a melting pot for knowledge breeding since it carries special characteristics that emulate spoken expression via explicit spelling. Furthermore, the inclusion and blending of tacit and explicit knowledge are contributing to the Socialization and Externalization process in knowledge management as proposed by Nonaka’s knowledge creation model.